The Meaning of Local Cultural Values ​​Siri' na Pacce in Managerial Accounting Decision Making: Qualitative Study of Business Actors in Makassar City - Sri Depi; Amiruddin; Rahmawati Hs (Yayasan Amerta Insan Unggul, 2026)
This study aims to examine the role of local cultural values, specifically Siri’ na Pacce, in shaping managerial accounting decision-making among business actors in Makassar City. The research adopts a qualitative approach using a phenomenological method to explore the subjective meanings and lived experiences of business practitioners within their socio-cultural context. Data were collected through in-depth interviews, observations, and relevant documentation, and analyzed using an interactive qualitative analysis model involving data reduction, data display, and conclusion drawing. The findings reveal that managerial accounting decisions are not solely driven by economic rationality but are significantly influenced by cultural values embedded in the Bugis-Makassar society. The concept of siri’ (self-esteem and dignity) encourages integrity, honesty, and the preservation of business reputation, while pacce (empathy and social solidarity) promotes social responsibility and ethical considerations in business practices. Consequently, accounting practices tend to be contextual, adaptive, and not always aligned with formal accounting standards, as they are shaped by social interactions, experiences, and local norms. This study contributes to the development of indigenous accounting literature by highlighting accounting as a socially constructed practice influenced by cultural and psychological factors. The findings suggest the need for a more culturally responsive and context-based managerial accounting approach to enhance its relevance and effectiveness in diverse socio-cultural environments.